دور مؤسسات الرعاية الاجتماعية في تأهيل ذوي الاحتياجات الخاصة دراسة ميدانية بالمركز الطبي التربوي بولاية قالمة - حواوسة, جمال (University of Eloued جامعة الوادي, 2019)
هدفت هذه الدراسة إلى التعرف على دور مؤسسات الرعاية الاجتماعية في تأهيل ذوي الاحتياجات الخاصة، من خلال الكشف على نوعية البرامج والوسائل والخدمات المقدمة لهم، وطبيعة التأهيل الذي يحظون به داخل هذه المؤسسات، ولتحقيق هذا الهدف أجريت دراسة ميدانية بالمركز الطبي التربوي بولاية قالمة على عينة مكونة من 30 مبحوث من المتعاملين بطريقة مباشرة مع فئة ذوي الاحتياجات الخاصة. وتوصلت الدراسة إلى أنه بالرغم من تعدد الخدمات المقدمة لذوي الاحتياجات الخاصة فإنها لم تصل إلى المستوى المطلوب، وهذا راجع إلى ضعف الميزانية، وقلة وسائل التأهيل، وغياب الكوادر المتخصصة، وعدم تناسب بعض البرامج مع قدرات المعاقين. Abstract: This study aimed to identify the role of social welfare institutions for the rehabilitation of persons with special needs, through disclosure on the quality of the programs, means and services provided to them, and the nature of rehabilitation, which are within these institutions in order to achieve this goal, conducted a field study in the medical center of education in the state of Guelma, on a sample of 30 researched from dealing directly with the category of persons with special needs. The study concluded that despite the multiplicity of services provided to persons with special needs, it did not reach the required level, which refer to the weakness of the Budget, the lack of rehabilitation, and the absence of specialized cadres, and suitable for some programs with the capabilities of the disabled
The role of social welfare institutions in the rehabilitation of persons with special needs. Field study in the medical Center of education in the state of Guelma
مجلة الدراسات والبحوث الاجتماعية المجلد 07 العدد 01 جامعة الوادي
Keywords: الدور، مؤسسات الرعاية الاجتماعية، التأهيل، ذوي الاحتياجات الخاصة.; role, social welfare institutions, rehabilitation, with special needs.